Elements of Digital Technology Needs Among Technical and Vocational Education Students - Abdullah, Aina Fatihah; Jambari, Hanifah; Taman, Ishak; Pairan, Mohamad Rasidi; Osman, Sharifah; Mohd. Ahyan, Nurul Aini (Online Journal for TVET Practitioners, 2023)
This study was conducted to identify digital technology needs among final year students of Technical and Vocational Education (TVE) at the School of Education, Universiti Teknologi Malaysia (UTM)-. The elements selected for this study are the students' technical skills, attitudes and the availability of facilities. A questionnaire was used as a research instrument in this quantitative study. A total of 89 respondents were selected at random. The collected data was analyzed using the Statistical Package Social Sciences (SPSS) software version 26.0 to obtain frequency values, percentages (%), means, and standard deviations. According to the findings of the study, the need for digital technology among final-year TVE students is satisfactory, with the mean value for the entire research question obtained being 3.50 at a moderate score level. Therefore, the School of Education at UTM needs to increase the need for the use of digital technology to facilitate students in the teaching and learning process.